O czym pamiętać, pytając o rzeczy trudne? : Refleksja metodologiczna nad badaniami zagadnień wrażliwych (Politeja, 2020)
What to Remember When Asking About Difficult Issues? Some Remarks on the Methodology of Sensitive ResearchDealing with sensitive topics in social science research has a distinct and well established tradition, and post-memory studies may fall into this category as well. The paper focuses on practical issues connected to qualitative interviewing on sensitive topics. In detail, it bridges the gap between psychological literature and practice, primarily counselling psychology, and scholarship on sensitive topics present in many areas of sociology. The main problems that a researcher may face while conducting interviews on sensitive issues lay in or are connected to the structure of the interview, the resistance of the informant as well as the authenticity and personal communication competences. Attention is devoted to ethical issues present in this category of research.